Spatial Hearing in Children With and Without Hearing Loss: Where and What the Speech Is Matters for Local Speech Intelligibility. - Pittman, Andrea L.; Pastore, M. Torben (American Journal of Audiology, 2024)
Purpose: This study examined children's ability to perceive speech from multiple locations on the horizontal plane. Children with hearing loss were compared to normal-hearing peers while using amplification with and without advanced noise management. Method: Participants were 21 children with normal hearing (9-15 years) and 12 children with moderate symmetrical hearing loss (11-15 years). Word recognition, nonword detection, and word recall were assessed. Stimuli were presented randomly from multiple discrete locations in multitalker noise. Children with hearing loss were fit with devices having separate omnidirectional and noise management programs. The noise management feature is designed to preserve audibility in noise by rapidly analyzing input from all locations and reducing the noise management when speech is detected from locations around the hearing aid user. Results: Significant effects of left/right and front/back lateralization occurred as well as effects of hearing loss and hearing aid noise management. Children with normal hearing experienced a left-side advantage for word recognition and a right-side advantage for nonword detection. Children with hearing loss demonstrated poorer performance overall on all tasks with better word recognition from the back, and word recall from the right, in the omnidirectional condition. With noise management, performance improved from the front compared to the back for all three tasks and from the right for word recognition and word recall. Conclusions: The shape of children's local speech intelligibility on the horizontal plane is not omnidirectional. It is task dependent and shaped further by hearing loss and hearing aid signal processing. Front/back shifts in children with hearing loss are consistent with the behavior of hearing aid noise management, while the right-side biases observed in both groups are consistent with the effects of specialized speech processing in the left hemisphere of the brain.